Collective transportation of objects by a swarm of robots - Torabi, Sina (My University, 2015)
A collective transport strategy, inspired by the food retrieval procedure of ant colonies, has been implemented on a swarm of robots that are smaller than the object. A simple odometry-based team coordination strategy in combination with an omni-directional camera has been implemented, resulting in a well-coordinated e ort by the robots without using any communication. The strategy is fully decentralized. Moreover, a simple recruitment process has been introduced but it did not improve the transportation efficiency. The transportation strategy consists of four stages, namely prey discovery, team coordination, recruitment, and transportation. A simulation environment capable of handling robot swarms and their physical interaction is developed for this project. Using robots weighing 3 kg, a 3 kg object was successfully transported in 48 out of 50 trials, whereas a 4.5 kg object was successfully transportedin 44 out of 50 trials.
Keywords: Annan teknik; Other Engineering and Technologies